2023
DOI: 10.3390/land12051038
|View full text |Cite
|
Sign up to set email alerts
|

Township, County Town, Metropolitan Area, or Foreign Cities? Evidence from House Purchases by Rural Households in China

Abstract: In the context of China’s New Urbanization Strategy, it is of great practical significance to study rural–urban population migration from the perspective of house purchases by rural households. In this paper, the Huai’an Rural Survey Dataset (872,414 households) was used to study the heterogeneity of rural households’ house purchases in different classes of urban destinations, and its influencing factors were analyzed with GeoDetector. The results show that the urban house purchase destinations preferred by fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Economic factors, serving as the primary impetus for population migration, stand as the focal point in immigration research. A number of studies have shown that the improvement in family economy, job income, and housing conditions will significantly increase the urban settlement intention of the floating population [46][47][48][49][50][51][52]. This paper proposes Hypothesis 1-1: The economic life satisfaction of the floating population will have a signif-icant positive impact on their urban settlement intention, which is closely related to family economy, job status, and housing status.…”
Section: Model Structure Of Human Capital Life Satisfaction and Urban...mentioning
confidence: 91%
“…Economic factors, serving as the primary impetus for population migration, stand as the focal point in immigration research. A number of studies have shown that the improvement in family economy, job income, and housing conditions will significantly increase the urban settlement intention of the floating population [46][47][48][49][50][51][52]. This paper proposes Hypothesis 1-1: The economic life satisfaction of the floating population will have a signif-icant positive impact on their urban settlement intention, which is closely related to family economy, job status, and housing status.…”
Section: Model Structure Of Human Capital Life Satisfaction and Urban...mentioning
confidence: 91%
“…Since reform and opening up, China's 'economic growth miracle' and rapid urbanisation have produced a historic structural transformation [1,2]. In the process of rapid economic change, a large number of rural migrant workers have moved to the cities and have gradually taken up permanent residence there [3].…”
Section: Introductionmentioning
confidence: 99%